Do school curricula matter to students in the long run? The case of teaching the theory of evolution or creationism in the United States - Benjamin W. Arold (EconPol Forum, 2023)
The teaching of evolution theory in school has a lasting impact on students. Reforms of the coverage of evolution in US education standards have a positive effect on students' knowledge of evolution by the end of high school. These reforms translate into a greater belief in evolution in adulthood, without crowding out religiosity or affecting political attitudes. They also affect high-stakes life decisions, such as the probability of choosing a career in life sciences. These findings imply that science education is an effective tool for fostering scientific attitudes and tackling the shortage of STEM workers
Keywords: 330